Analysis of the Financial Performance of the Government of Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency for the 2020-2022 Period - Sarra, Siti; Iskandar Sam; Misni Erwati (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to determine the financial performance of the Tangkit Baru Village Government by using the Degree of Decentralization, Regional Financial Dependency, and Regional Financial Independence, Village Original Income Effectiveness Ratio and SWOT Analysis. This research is quantitative descriptive using secondary data consisting of Tangkit Baru Village Revenue and Expenditure Budget Realization Report for the 2020-2022 Period. The research results show that the Degree of Financial Performance of the Tangkit Baru Village Government is based on Decentralization Ratio is categorized as extremely poor, The Village Original Income Ratio is quite effective, and the regional financial dependency ratio is very high; the regional financial independence ratio is very low and involves an educational relationship pattern